Social capital, absorptive capacity and entrepreneurial behaviour in an international context. (2016) - Castro, Ignacio; Cepeda, Gabriel
This study proposes a learning-based model that contributes to understanding the international growth of small and medium-sized enterprises. It shows the influence of the social capital of the firm on external access to and exploitation of knowledge and how this in turn affects entrepreneurial orientation. This model is tested with structural equation modelling (Partial Least Squares) applied to a sample of 178 international Spanish firms. Our results emphasise, on the one hand, the importance of managing inter-organisational relationships in the learning processes of the firm and, on the other, how knowledge exploitation exerts a significant influence on the firm's entrepreneurial behaviour and, therefore, how it is a decisive force in international expansion.